Social Networks for Learning: Performance Expectancy Vs Social Influence - Boidou, Blaise Noël; Agbanglanon, Sylvain Luc; Coulibaly, Mélama; Adjanohoun , Jonas Alexandre Dominique (International Journal of African Higher Education, 2024)
This article examines the factors that determine students’ acceptance of social networks for learning at the Virtual University of Côte d’Ivoire. It investigates whether the expected added value in terms of performance was the primary factor motivating their adoption in learning or training activities. The Unified Theory of Acceptance and Use of Technology model was adopted as the theoretical framework, with data gathered by means of an online survey, to which 315 students responded, and analysed using a partial least squares structural model. The study found that the intention to use social networks for learning is primarily determined by effort expectancy, while social influence is the second most important determinant. While performance expectancy was found to be the least important factor, the results show that it had a positive effect on men’s intention to use social networks for learning, but a negative effect for women.